Acoustic radiation force impulse imaging with Virtual Touch™ tissue quantification: mean shear wave velocity of malignant and benign breast masses - Wojcinski S; Brandhorst K; Sadigh G; Hillemanns P; Degenhardt F (Dove Medical Press, 2013)
Sebastian Wojcinski,1 Kathrin Brandhorst,2 Gelareh Sadigh,3 Peter Hillemanns,1 Friedrich Degenhardt2 1Department of Obstetrics and Gynecology, Hannover Medical School, Hannover, Germany; 2Department of Obstetrics and Gynecology, Franziskus Hospital, Bielefeld, Germany; 3Department of Radiology, Emory University, Atlanta, GA, USA Abstract: Acoustic radiation force impulse imaging (ARFI) with Virtual Touch™ tissue quantification (VTTQ) enables the determination of shear wave velocity (SWV) in meters per second (m/s). The aim of our study was to describe the mean SWV in normal breast tissue and various breast masses. We performed measurements of SWV with ARFI VTTQ in 145 breast masses (57 malignant, 88 benign) and in the adjacent breast parenchyma and adipose tissue. The mean SWV as well as the rate of successful measurements were analyzed. The difference between adipose tissue and parenchyma was statistically significant (3.05 versus 3.65 m/s) (P < 0.001). Focusing on breast masses, numerous measurements exceeded the upper limit of possible measurement (≥9.10 m/s, indicated as "X.XX m/s"). Nevertheless, the difference between the malignant and benign masses was statistically significant (8.38 ± 1.99 m/s versus 5.39 ± 2.95 m/s) (P < 0.001). The best diagnostic accuracy (75.9%) was achieved when the cutoff point for malignancy was set to 9.10 m/s in ARFI VTTQ. This implies that the SWV was regarded as suspicious when the upper limit of possible measurement was exceeded and the machine returned the value X.XX m/s. In conclusion, ARFI VTTQ is a feasible method for measurement of SWV in a region of interest. Furthermore, we propose the event of a highly elevated SWV as a significant criterion for malignancy. However, the method is technically not yet fully developed, and the problem of unsuccessful measurements must still be solved. Keywords: ARFI VTTQ, elastography, ultrasound, breast imaging